Responsibility of Transportation Companies for Loss of Consumer Goods in Transportation Activities (Study: PT. Maharani Prema Sakti Denpasar) - SANCAYA, I Wayan Werasmana; LARASDIPUTRA, Deny (Journal of Tourism Economics and Policy, 2025)
This study discusses the form and implementation of the responsibility of transportation companies for the loss of consumer goods during transportation activities, with a case study at PT. Maharani Prema Sakti Denpasar. The background of the study is based on the increasing cases of lost goods during the shipping process which cause losses to consumers and raise legal issues regarding the limits of responsibility of transportation companies. This study uses an empirical legal method with a socio-legal approach, to examine how legal provisions such as the Civil Code, Law Number 8 of 1999 concerning Consumer Protection, and Law Number 22 of 2009 concerning Road Traffic and Transportation are applied in practice. The research results indicate that the responsibility of a shipping company is essentially absolute from the time the goods are received until they are delivered to the recipient, unless the loss occurs due to force majeure or the negligence of the shipper. At PT. Maharani Prema Sakti Denpasar, the implementation of responsibility is carried out through internal procedures such as implementing SOPs for packaging and arranging goods, processing compensation claims, and resolving disputes amicably. The company does not provide specific insurance but instead directs consumers to insure their goods independently. This research concludes that although the liability system is functioning well, there is a need to improve legal protection for consumers through the integration of insurance mechanisms and strengthening oversight of regulatory implementation.